Noticing the unusual: a self-prompt strategy for adults with autism. Issue 2 (29th October 2015) - Silver, Kate; Parsons, Sarah
Abstract : Purpose: – There is a substantial lack of research focusing on how to support the social understanding of high-functioning adults with autism (HFA). The perspectives of three adults with HFA were used to develop and implement self-prompt systems to increase knowledge and awareness of social situations. The paper aims to discuss these issues. Design/methodology/approach: – Semi-structured interviews and diaries were used to support individuals to reflect on video-based and real-life social situations, within a qualitative participatory case study design. Qualitative data were analyzed thematically. Findings: – Participants developed and used a self-prompt system to support their social understanding in a range of situations. "Noticing the unusual" in social situations, consideration of the potential impact of others' behavior on them personally, and guessing the intention of others were identified as useful strategies. Basing social judgments on the facial expressions of others was not useful. Research limitations/implications: – This was a small-scale study with only three high-functioning participants and so the research needs to be extended to a wider group. Practical implications: – There is considerable potential for this approach to be used with adults accessing support services because the strategies identified can be easily applied and personalized. Social implications: – Independent, unplanned use of the self-prompt strategy enabled participants to reduce dependence on others in social situations through supporting their independent thinking and actions. Originality/value: – This study moves away from a deficit-focussed model of intervention to one that seeks to uncover strengths in order to empower individuals to use their existing knowledge.